Prevalensi COVID-19 Derajat Berat dan Kritis saat Admisi pada Pasien Penyakit Reumatik Autoimun dan Faktor-Faktor yang Berhubungan - Destini, Mulia; Ariane, Anna; Yulianti, Mira; Rizka, Aulia; Rinaldi, Ikhwan; Mansjoer, Arif; Maulahela, Hasan; Wafa, Syahidatul (UI Scholars Hub, 2026)
Introduction. Patients with autoimmune rheumatic diseases are known to be more vulnerable to severe and critical infections, including COVID-19. Although it is no longer classified as a pandemic, SARS- CoV-2 infection still persists, and several surges of cases have been reported, including in Indonesia. To date, no data are available regarding the prevalence of severe and critical COVID-19 at admission in patients with autoimmune rheumatic diseases in Indonesia and the associated factors. This study aimed to determine the prevalence of severe and critical COVID-19 at admission in patients with autoimmune rheumatic diseases at Dr. Cipto Mangunkusumo National General Hospital, and to identify the associated factors. Methods. This was a cross-sectional study using secondary data from the medical records of patients with autoimmune rheumatic diseases confirmed with COVID-19 and hospitalized at Dr. Cipto Mangunkusumo National General Hospital between July 2020 and August 2024. Analyses were performed up to multivariate logistic regression to evaluate the association between predictor variables and severe and critical COVID-19 at admission. Results. Among 171 subjects, the majority were female (n=158). The median age was 31 years, ranging from 18 to 74 years. The prevalence of severe and critical COVID-19 at admission in patients with autoimmune rheumatic diseases was 41.5%. Routine corticosteroid use (adjusted prevalence ratio (aPR) 2.58; 95% CI 1.40–5.17; p=0.004), the presence of comorbidities (aPR 2.24; 95% CI 1.19–4.59; p=0.018), moderate–high disease activity (aPR 5.12; 95% CI 1.74–21.96; p=0.009), and combination immune-modifying therapy (aPR 1.79; 95% CI 1.06–3.17; p=0.034) were independently associated with severe and critical COVID-19 at admission in the final multivariate analysis. Conclusions. The prevalence of severe and critical COVID-19 at admission in patients with autoimmune rheumatic diseases was 41,5%. The associated factors were routine corticosteroid use, the presence of comorbidities, moderate–high disease activity, and combination immune-modifying therapy.